Sozialhilfe, Lohnabstand und Leistungsanreize - Alfred Boss (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1999)
The difference between the potential net wage income (including family allowances etc.) and the social welfare payments is measured for a large number of types of private households in the Federal Republic of Germany in 1998. It is shown that the difference is small for households consisting of at least three persons. For three types of households the difference between net wages and social assistance is measured for the 1962-1998 period. It turns out that it decreased significantly in the course of the decades. Independently of the household type, the (explicit and implicit) marginal tax rates for wage income amount to 100 percent for relatively large income intervals. Thus, the incentives to work seem to be strongly impaired. There is evidence that the adjustment of wages for low skilled workers in Germany was impeded by the system of social assistance.
Keywords: H31; H53; 330; social assistance; incentives to work; poverty trap; Sozialhilfe; Lohn; Grenzsteuersatz; Steuerbelastung; Arbeitsangebot; Deutschland